Desarrollo de algoritmos para modelado de rutinas de ejercicios para rehabilitación física en mejora de la calidad y esperanza de vida de adultos mayores implementados en robot humanoide Nao. - Achig Ortiz, Ángel Omar (2017)
The present project focuses mainly on the development of algorithms based on programming language, for the modeling of different types of physical exercise routines that help improve the quality and life expectancy of the elderly. Another type of algorithm was developed so that the android can hold broadcast and receive conversations of messages previously designed in a menu of the general process. Practically the algorithms elaborated as such, allow the intelligent robot to perform several movements simulating a physical exercise, allowing the user to select any of these and perform it according to their physical state. It should be mentioned that physical activity was supervised and controlled through the application of correction of postures, which verified and indicated that the same were correctly performed by the person and are in accordance with the exercise manual prescribed by a professional in physiotherapy. On the other hand if these are incorrectly executed it is analyzed and indicates that they are wrong, allowing the person to correct in a set time.